Pemanfaatan Blog sebagai Media Pembelajaran B. Indonesia pada Kelas 5 SD/MI - Elok Faiqoh Achmad Syaichun; Mery Sabilla Faqih (Jurnal Gentala Pendidikan Dasar, 2022)
This modern era is determined by the rapid development of technologyinformation, this also has an impact on the education sector. Internethas become an alternative way to search for all kinds ofinformation needed by teachers and students, there is no space limitand time for this type of technology, the teaching and learning process becomesmore flexible, teachers and students can find themselves outsideclasses and regular time schedules, especially students nowalready familiar with technology, they bring gadgets insideclass, sometimes, they use it for their businessalone, when the teacher is explaining something, the teacher must be creativefacilitate not only the demand for internet technology andalso to improve the teaching of the learning process, hereThe author proposes blogs as an alternative media,With this media, students can explore the posted materialby the teacher on the blog. Students can study anywhere and anytime.which is certainly very different from conventional learning.Blog is one of the technology-based learning mediaInformation and Communication (ICT). By using blog mediaexpected to create active learning, creative,effective and fun. Use of blogs as medialearning has the advantage of readily available informationbroad, fast, and precise, there is convenience in the learning processand technology support to facilitate the learning processteach. The application of ICT also has a distinctive advantage, namely that it does notlimited by place and time.